Implikasi Perubahan kurikulum terhadap Kompetensi Pedagogik Guru Pendidikan Agama Islam - Muliya Maulidina; Nurfuadi (Jurnal Dirosah Islamiyah, 2024)
Indonesia has made several curriculum changes to date. Of course, this change did not happen suddenly, but went through several processes. There are several factors that cause curriculum changes, one of which is policy changes. This curriculum change was made of course with the hope that it would provide positive value for Indonesia's progress. This article will discuss the implications of changing the 2013 curriculum policy to the Merdeka curriculum. Especially the influence on PAI teachers' pedagogic competence